2019
DOI: 10.5194/asr-15-263-2019
|View full text |Cite
|
Sign up to set email alerts
|

Towards a definitive historical high-resolution climate dataset for Ireland – promoting climate research in Ireland

Abstract: Abstract. There is strong and constant demand from various sectors (research, industry and government) for long-term, high-resolution (both temporal and spatial), gridded climate datasets. To address this demand, the Irish Centre for High-End Computing (ICHEC) has recently performed two high-resolution simulations of the Irish climate, utilising the Regional Climate Models (RCMs) COSMO-CLM5 and WRF v3.7.1. The datasets produced contain hourly outputs for an array of sub-surface, surface and atmospheric fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Extensive validations were carried out to test the ability of the RCMs to accurately model the climate of Ireland. Results confirm that the output of the RCMs exhibit reasonable and realistic features as documented in the historical data record Flanagan et al, 2019;Werner et al, 2019).…”
Section: Regional Climate Model Validationsupporting
confidence: 80%
See 4 more Smart Citations
“…Extensive validations were carried out to test the ability of the RCMs to accurately model the climate of Ireland. Results confirm that the output of the RCMs exhibit reasonable and realistic features as documented in the historical data record Flanagan et al, 2019;Werner et al, 2019).…”
Section: Regional Climate Model Validationsupporting
confidence: 80%
“…It was found that although the RCM accuracy increased with a higher spatial resolution, reducing the horizontal grid spacing below 4 km provided relatively little added value (Nolan et al, 2017). The results of the preliminary experiments determined the model configurations of the current study (Nolan et al, 2017;Flanagan et al, 2019).…”
Section: Model Domains and Experiments Setupmentioning
confidence: 63%
See 3 more Smart Citations